A double spherical 6R linkage with spatial crank-rocker characteristics inspired by kirigami. (November 2020) - Liu, Weiqi; Chen, Yan
Highlights: A special double spherical linkage inspired by origami is proposed. Detailed kinematic analysis of the double spherical 6 R linkage is presented. The crank-rocker characteristics and bifurcation behaviours was analysed. The motion path of the alternative origami forms was revealed. Abstract: Grashof linkage was well studied in planar and spherical 4 R linkage. In this paper, this characteristic is associated with a spatial linkage evolved from an kirigami loop. Both the overconstrained geometric conditions and the explicit closure equations are derived with the D-H method. It is found out that the 6 R overconstrained linkage can work as a crank-rocker or a double crank linkage. Its bifurcation behaviours under two motion modes are analysed. We further transfer this 6 R linkage back into the kirigami form and discuss its kinematic behaviours such as spatial 8-shaped trajectories. This work sets up the bridge between the spatial linkages and rigid kirigami forms to develop emerging kinematic behaviours.